An Assessment of Household’s Out of Pocket Healthcare Payment and Impoverishment in Nepal: Evidence from Nepal Living Standard Survey III - Thapa, Arjun K. (Journal of Development and Social Engineering, 2017)
Despite Government of Nepal’s effort of universalizing basic free health care services and other demand side financing health schemes, there is an ongoing debate regarding equity in health service coverage, availability and high out of pocket payment. So this study intends to assess out of pocket payment and its associated factors and its implication on impoverishment. A cross sectional descriptive study was designed which is based on Nepal Living Standard Survey III 2010/11, a rich and well representative secondary data of Central Bureau of Statistics, National Planning Commission Nepal. The information about individuals who reported out of pocket healthcare payment was extracted from 28,747 individuals (or 7,020 households) of the survey. An individual from a household is considered as the unit of study. The major findings of the study show that age, caste ethnicity, place of residence, ecological belt and development region have statistically significant association with OOP payment. Due to OOP expenditure near about 3 percent of people are falling below the poverty line. The impoverishment rate is high among people residing in rural areas (3.4%), Terai belt (3.4%) and Eastern development region (3.7%). Higher impoverishment level in Terai and Eastern development region where health facilities are fairly available in comparison to remote Mountain belt, low developed Far west and Mid-west only signifies low availability and utilization of health services. So there is a need to address lacunae in fair coverage and utilization of health services across the country along with impoverishment.